Using Title IX and the Model of Public Housing to Prevent Housing Discrimination Against Survivors of Sexual Assaults on College Campuses - Cleary, Shannon (Columbia Journal of Gender and Law, 2015)
At the time of its passage, the vast scope of Title IX of the Education Amendments of 1972 was virtually unknown.1 Bernice Sandler, a women’s rights activist who helped draft Title IX, noted that Oregon congresswoman Edith Green, one of the bill’s sponsors, shunned the idea of lobbying for Title IX.2 Lobbying, she explained, would lead to questions and to people finding out what Title IX could actually do; instead, when Title IX passed, the law became, in Sandler’s words, “a big break that no one was watching.”3 Initially, Title IX was used to require that universities provide athletic opportunities for women and men that are proportionate to their rates of enrollment.4 Now, over forty years later, Title IX is being utilized in a new way that shows just how big a break its passage really was: Title IX is now a way to sue colleges for not protecting their students from sexual assault and the trauma survivors face during subsequent disciplinary proceedings. Title IX provides that, “no person in the United States shall, on the basis of sex, be excluded from participation in, be denied the benefits of, or be subjected to discrimination under any education program or activity receiving Federal financial assistance.”5 By late July 2015, the United States Department of Education Office of Civil Rights (OCR) had announced that 124 colleges were under federal investigation for violating Title IX through their handling of sexual assault cases, including such elite institutions as Harvard College, Columbia University, Dartmouth College, and Brown University.6 While much of the focus of these investigations has been the reporting mechanisms in place for students and the disciplinary procedures that colleges use to determine whether an alleged perpetrator should be removed from campus, another important reality of college sexual assaults is that survivors and their assailants often both live within the campus community. For survivors of assault, living in close proximity to their assailants and knowing that their assailants could, at any time, swipe their access card and enter the dormitories where survivors live may be debilitating, causing feelings of intense fear, anger, guilt, shame, or panic.7 I will therefore argue in this Note that Title IX compliance must include procedures for guaranteed safe housing after an assault. Because so few students do file complaints with their universities, I will argue that these procedures should be available regardless of police involvement or whether a student files a formal complaint. In Part I, I will explain how sexual assaults fit within the Title IX framework of discrimination. In Part II, I will provide a brief history of how Title IX has been used in response to campus sexual assaults in the lead up to the current wave of complaints. I will also give an overview of the OCR guidelines regarding how colleges and universities should handle reports of sexual assaults within their campus communities and what the role of housing has been in complaints thus far. In Part III, I will analyze a campus survey conducted at the Massachusetts Institute of Technology (MIT) to show how current reporting mechanisms are underutilized for a variety of reasons, including the inability of survivors to label their experiences. In Part IV, I will examine how public housing attempts to ensure the safety of residents who are survivors of domestic violence. Lastly, in Part V, I will show how public housing policies can be adapted to fit within a university system, guiding how and when universities can move students accused of assault and ways to move complainants that are not stigmatizing or isolating. Such policies could limit discrimination against survivors who seek safer housing that does not impair their access to education and will give universities more guidance on how to comply with Title IX.